Isu-Isu Sosial Dan Etika Dalam Sistem Ekonomi - Sarahfina; Selvi Irene Claudia; Riskia Ramadhani; Nur Fitriana (Jurnal Ekonomi dan Bisnis Digital, 2024)
Social and ethical issues that arise in the context of the economic system. Economics is not only about the efficient allocation of resources, but also about how economic decisions affect society as a whole. Issues such as inequitable income distribution, unequal access to basic services, and the social impact of economic policies are some of the major issues faced. The study also explores various ethical dilemmas that arise in economic and business practices, as well as the importance of integrity and social responsibility in economic decision-making.